Me quiseram rosa, subjugaram meus espinhos: mulheres rés e relações de gênero na Comarca de Castro, Paraná (1840-1890) - Meira, Ana Paula Galvão de (2021)
This research is about women who differed from the profile and behavior associated with the female gender, in the District of Castro, Paraná, from 1840 to 1890. We tried to analyze the trajectory of women who, at some point in their lives, were traversed by the legal discourse, disrupting the norms of the dominant models in gender and social relations. Through the practices of violence and misdemeanors, the women of the 19th century castrense community and that make up the body of this thesis, experienced deviant and reprehensible femininities, forged in the very discourse that constructed them with elements attributable to the “female nature”. The work seeks to highlight the production of gender markers, considering the effects caused in authorized knowledge , such as the case of legal knowledge, medical knowledge and religious knowledge, which directly influenced/influenced the construction of models of femininity and masculinity. Through the bias of gender studies, it was possible to identify the construction of these models of femininity and masculinity, which feature the use of biological demarcators as insurmountable and irrefutable. Thinking about the social production of the female woman, the australian sociologist Raewyn Connell introduced the concept of emphasized femininity and hegemonic masculinity, which allowed during this work the visibility of the subjectivities that escaped such imposition and/or expectation of the social practice of the female and male genders. Michel Foucault helped us to interpret the sources, which are expressly institutional, being these criminal cases, medical journals, government reports and parish records, in which we perceive the constitution of the subjects by/in the discourse. By analyzing the practices of women's violence in the Comarca of Castro, during the period (1840-1890) , we seek to elucidate the gender relations and social relations that touched the subjectivities, actions and experiences of these women and what led them to be disqualified as women and perceived as criminals.